PENGARUH FEE AUDIT, AUDIT TENURE, ROTASI AUDIT DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT - Muhamad Rafly Herdiansyah; Dirvi Surya Abbas; Imam Hidayat; Mohammad Zulman Hakim (Akuntansi, 2022)
This research was conducted to test the effect of variables of Company Size, Fee Audit, AuditTenure, and Rotation audit on Audit Quality. The sample in this study amounted to 59 primaryconsumer sector companies listed on the Indonesia Stock Exchange for the period 2018-2020which were selected based on purposive sampling methods and also referred to the selectedcriteria. The sample data was obtained by 59 companies with a total sample of 177. The qualityof audits in the study was measured using a proxy of the size of a public accounting firm. Theanalysis technique used is logistic regression with a significance rate of 5%. The results showedthat (1) The Size of the Company had a significant positive effect on audit quality (2) Fee Audithad a significant effect on audit quality (3) audit tenure had no significant effect Positive toAudit Quality (4) Audit Rotation has no effect on Audit Quality.